PENGEMBANGAN MEDIA FLASH CARD SEBAGAI INOVASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Fudhla, Mahmudatun; Nurselly, Tania Tiara; Al-Khuzaiyah, Ma’bad; Nadhiroh, Lutfin (Maliki Interdisciplinary Journal, 2025)
This study aims to develop interactive flash card learning media called Sirah Card of Isra’ Mi’raj as an innovative solution to improve the quality of Islamic Cultural History learning. The background of this media development is the lack of student interest in learning Islamic Cultural History which tends to be monotonous and lacks visualization. This study uses the Research and Development (R&D) method to design and test the effectiveness of the media. The media is packaged in the form of an educational card containing a QR barcode connected to a short narrative video about the story of Isra’ Mi’raj. The trial results show that this media is effective in improving students’ understanding of the content of the material, strengthening memory of the sequence of events, and increasing students’ active involvement in the learning process. Teachers also feel the ease and effectiveness of using this media. Therefore, Sirah Card of Isra’ Mi’raj is considered worthy of being used and further developed as a technology-based and visualization-based Islamic Cultural History learning media.